TYPOLOGI DAN POTENSI PENERIMAAN PAJAK REKLAME DI KOTA PONTIANAK - B61111020, Heri Ahmad Sattari (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT Keywords : Typologi Klasen , potency , effectiveness , effort , and capacity Taxes Reklamel tax as a source of local revenue in Pontianak during the period 2008-2012 have not provided significant results , where the contribution to revenue by an average of 0:08 % per year , with the realization that always exceeds the target with numbers above 100 % , but was associated with the development social and economic variables such as GDP growth rate, per capita income and value -added sub- sectors Advertising , its contribution should still be improved . Advertising Tax targeting yet realistic , be one contributing factor , because the revenue target should be based on the potential or capacity is generally assessed based only ( approximate ) , so it's not impossible the realization of acceptance by a ratio of more than 100 % it is not optimal . In connection with the above , this thesis intends to determine the position of the advertisement tax dengaan typologi Klasen and calculate the real potential of advertisement tax , the level of effectiveness : tax effort (tax - effort) and the capacity of the tax , then through a system of tax collection procedures Advertising and city government Pontianak will have objective guidelines in determining a target , and if there is a gap between the realization of the targets can be created strategies to optimize tax revenues advertisement . The approach taken to answer the research objectives of this thesis , especially to measure the magnitude typolgi Klasen and find out the real potential of advertisement tax in year t , obtained by Linear Trend Analysis , Level of Effectiveness estimated in a straightforward manner that the ratio between the proceeds received by the target acceptance and Hotel tax real potential in order to obtain the capacity ratio (tax - capacity) and the tax effort (tax - effort) . The results showed that the typologi Klasen Advertising Tax in Pontianak was in Developing sector , while the results of the calculation of potential besadarakan advertisement tax by an average of 4,218,153,656 with the level of effectiveness based on the target or its tax- capacity average of 110 percent per year , but the level of effectiveness based on potential or its tax -effort by 98 percent per year